GRAMMATICAL AND STYLISTIC CHARACTERISTICS OF ADVERTISEMENTS IN UZBEK AND ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the grammatical and stylistic characteristics of advertising texts in Uzbek and English. The study examines advertising discourse as an important means of communication that combines informative, persuasive, emotional, and aesthetic functions. Particular attention is given to grammatical features such as imperative constructions, concise sentence structures, politeness forms, and direct appeals, as well as stylistic devices including metaphor, hyperbole, repetition, alliteration, assonance, pun, and phraseological expressions. The research also explores the role of euphemisms and neologisms in creating positive associations and expressing innovation in advertising language. A comparative analysis demonstrates that Uzbek advertisements mainly emphasize national values, politeness, and emotionality, while English advertisements focus on brevity, directness, humor, and individualism. The findings show that advertising language reflects not only commercial purposes but also cultural traditions, social mentality, and communication styles in different linguistic environments.
Keywords: advertising discourse, advertising language, stylistic devices, grammatical features, euphemisms, neologisms, Uzbek advertising, English advertising, persuasive communication, linguistic analysis.